The Crystal Structure of Dodecahedral Ba2+ Hexa-Perchlorate Complex Tetrakis 1-N-Propyl-3-vinyl-imidazol-1-ium·Barium Hexa-Perchlorate - Yuval Zertal; Natalia Fridman; Levi Gottlieb; Yoav Eichen (Molecules)
In cold methanol, energetic ionic liquid 1-n-propyl-3-vinyl-imidazol-1-ium perchlorate, 1, crystallizes in the presence of excess Ba(ClO4)2, 2, into tetrakis 1-propyl-3-vinyl-imidazol-1-ium·barium hexa-perchlorate, 3. Crystals of 3, with molecular formula (C8H13N2)4·BaCl6O24, are colorless and monoclinic, with space group P21/c. The crystal structure is characterized by a dodecahedral coordination around the barium atom, with each perchlorate chelating Ba2+ in a κ2O,O’ fashion, and the Ba(ClO4)64− anion is surrounded by four imidazolium cations.